2012
DOI: 10.1103/physrevb.85.060508
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous magnetotransport in the heavy-fermion superconductor Ce2PdIn8

Abstract: The normal state behavior in the heavy-fermion superconductor Ce2PdIn8 has been probed by means of Hall coefficient (RH) and transverse magnetoresistivity (M R) measurements. The results indicate the predominance of contributions from antiferromagnetic spin fluctuations at low temperatures. Anomalous non-Fermi-liquid-like features, observed below 8 K in both RH(T ) and M R(T ), are related to underlying quantum critical point, evidenced before in the specific heat and the electrical resistivity data. The magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…The most studied member of this series is the n = 1 member CeCoIn 5 (T c = 2.3 K) (16), in which clear evidence for non-FL behaviors in the normal state (17,18) and nodal superconductivity has been found (6,19,20). The recent discovery of superconductivity at ambient pressure in the n = 2 member Ce 2 PdIn 8 (T c = 0.68 K) (21), which exhibits very similar non-FL properties (22)(23)(24)(25)(26)(27) to those in CeCoIn 5 , allows a detailed comparison of the superconducting properties to extract common features in these superconductors near the antiferromagnetic QCP.…”
Section: Resultsmentioning
confidence: 99%
“…The most studied member of this series is the n = 1 member CeCoIn 5 (T c = 2.3 K) (16), in which clear evidence for non-FL behaviors in the normal state (17,18) and nodal superconductivity has been found (6,19,20). The recent discovery of superconductivity at ambient pressure in the n = 2 member Ce 2 PdIn 8 (T c = 0.68 K) (21), which exhibits very similar non-FL properties (22)(23)(24)(25)(26)(27) to those in CeCoIn 5 , allows a detailed comparison of the superconducting properties to extract common features in these superconductors near the antiferromagnetic QCP.…”
Section: Resultsmentioning
confidence: 99%
“…One may expect that spin fluctuations due to 4d electrons are also important for the emergence at low-temperatures of the unconventional superconducting state. Moreover, the coexistence of correlations of 4d and 4f electrons may lead to the quantum critical behavior reported for Ce 2 PdIn 8 [14][15][16][17][18][19][20][21][22][23].…”
Section: Valence Band Calculationsmentioning
confidence: 99%
“…In the course of subsequent studies, Ce 2 PdIn 8 has been characterized as an ambientpressure heavy-fermion superconductor with the onset of the superconducting state at T c = 0.68 K, strongly enhanced normal-state electronic specific heat coefficient γ ≈ 500 mJ/(mol K 2 ) per Ce atom, and distinct deviations from the Fermi liquid behavior evidenced in the electrical transport and thermodynamic properties [14][15][16][17][18][19][20][21], as well as in the spectroscopic characteristics: the nuclear quadrupole resonance [22] and inelastic neutron scattering [23] data. The superconducting state in this material has been found to possess a nodal character [19][20][21][22][23], most likely of d-wave type, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Non-Fermi-liquid behavior was observed in both macroscopic [6][7][8][9][10] and microscopic [11,12] measurements at low temperature, implying that Ce 2 PdIn 8 is located very close to a QCP. It was further suggested that a twodimensional (2D) SDW-type QCP is induced by magnetic field near the upper critical field, H c2 ≈ 2 T [9].…”
mentioning
confidence: 90%